Amorphous semiconductors - Kugler, Sándor, 1950-; Shimakawa, Koichi (Cambridge : Cambridge University Press, 2015)
Understanding the structural unit of crystalline solids is vital in determining their optical and electronic properties. However, the disordered nature of amorphous semiconductors, where no long-range order is retained, makes it difficult to determine their structure using traditional methods. This book shows how computer modelling can be used to overcome the difficulties that arise in the atomic scale identification of amorphous semiconductors. The book explains how to generate a random structure using computer modelling, providing readers with the techniques to construct realistic material structures. It shows how the optical and electronic properties are related to random structures. Readers will be able to understand the characteristic features of disordered semiconductors. The structural and electronic modifications by photon irradiation are also discussed in detail. This book is ideal for both physicists and engineers working in solid state physics, semiconductor engineering and electrical engineering.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Amorphous semiconductors; Semiconductors -- Computer simulation